Fabrication Quality Assessment Based on the Coupling of a Dual-Core Microstructured Polymer Optical Fiber - Amaia Berganza (MDPI AG, 2021)
In this paper we report on the theoretical analysis and fabrication of a dual-core microstructured polymer optical fiber (mPOF) and demonstrate how the coupling characteristics of a dual-core mPOF may be a key factor to assess the quality of the fabrication process. The coupling characteristics of this fiber have been tested and, for comparison purposes, simulations regarding the effects of inaccuracies during the manufacturing process were carried out to evaluate the fabrication quality. Results indicate that theoretical, simulation and experimental data are in good agreement, which highlights the uniformity of the microstructure along the fiber and the quality of its fabrication process. In fact, the manufactured mPOF reached a coupling efficiency up to 95.26%, which makes this mPOF appealing for applications in which highly efficient power couplers are required.